Trailblazer - Schmidt, Anna, 1943- (Schmidt, Anna, 1943- Cowboys & Harvey Girls., 2019)
With her family farm falling on hard times, Grace Rogers applies for a position with the prestigious Fred Harvey Company. Soon she's headed for Juniper, New Mexico to work in the Palace Hotel. There she meets a handsome cowboy who quickly turns her head. Too bad the Harvey Girls are forbidden to fall in love ... Nick Hopkins has a plan: buy a little land, marry, and raise a family--in that order. But after meeting Grace, he can't keep away. Their only choice is to marry in secret ... but between avoiding suspicion, family drama, and a rapidly changing Western frontier, can their love possibly survive?